Evaluation of Q angle in differents static postures - Sanchez,Hugo Machado (2014)
OBJECTIVE: To compare the value of Q angle in different positions, in the external and internal rotations of lower limbs. METHODS: This is a descriptive cross-sectional study. We have evaluated 62 volunteers, 32 women and 30 men in the following positions: supine positions with parallel feet, supine with abduction (external rotation of lower limbs), and standing position with parallel feet and with external rotation. All the participants were sedentary and without previous history of acute injury or complaints regarding lower limbs. In order to calculate the Q angle we used computerized biophotogrammetry through ALC image 2.1(r) program. RESULTS: The results of the comparisons showed significant difference between the standing position with feet parallel and orthostatic positions with abductees feet on the left side for both genders (p = 0.000). We also found a significant difference between supine and standing position with abducted feet and with feet parallel on the left side (p = 0.046) in females. CONCLUSION: From these results, we can conclude that there are significant differences in the standing position with abducted feet and parallel to the left leg, and symmetry between the lower limbs independent of rotation of limbs in the supine posture. Level of Evidence II, Diagnostic Studies Investigating a Diagnostic Test.